2001
DOI: 10.2174/1381612013397339
|View full text |Cite
|
Sign up to set email alerts
|

Beta3 -Adrenoceptor Agonists as Anti-diabetic and Anti-obesity Drugs in Humans

Abstract: In the early 1980s, an "atypical" beta-adrenergic receptor was discovered and subsequently called the beta (3)-adrenoceptor (beta(3)-AR). Agonists of the beta(3)-AR were observed to simultaneously increase lipolysis, fat oxidation, energy expenditure and insulin action leading to the belief that this receptor might serve as an attractive target for the treatment of diabetes and obesity. In vivo studies lent credence to this postulate with the finding that stimulation of this receptor by selective agonists lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 0 publications
1
73
2
Order By: Relevance
“…Observations of marked variation in the pharmacology of species orthologs of GPCRs are well known but are of particular relevance in the early stages of receptor characterization. For example, the differences in ligand affinity at the orthologs of the histamine H4 receptor (Liu et al, 2001) even led to suggestions that there might be other receptors for histamine and further detailed pharmacological characterization of various orthologs of this receptor (Lim et al, 2010;Schnell et al, 2011), and the development of early-generation ␤ 3 -adrenoceptor selective agonists was severely compromised by, at that time unappreciated, ortholog selectivity (de Souza and Burkey, 2001;Arch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Observations of marked variation in the pharmacology of species orthologs of GPCRs are well known but are of particular relevance in the early stages of receptor characterization. For example, the differences in ligand affinity at the orthologs of the histamine H4 receptor (Liu et al, 2001) even led to suggestions that there might be other receptors for histamine and further detailed pharmacological characterization of various orthologs of this receptor (Lim et al, 2010;Schnell et al, 2011), and the development of early-generation ␤ 3 -adrenoceptor selective agonists was severely compromised by, at that time unappreciated, ortholog selectivity (de Souza and Burkey, 2001;Arch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These agonists have been observed to simultaneously increase lipolysis, fat oxidation, energy expenditure and insulin action leading to the belief that this receptor might serve as an attractive target for the treatment of diabetes and obesity. However, drug design efforts have been hindered by the obstacles in the pharmacological differences between rodent and human ␤ 3 -AR, the lack of selectivity of leads, and unsatisfactory oral bioavailability and pharmacokinetic properties of tested agents (de Souza and Burkey, 2001). A recent test of ␤ 3 -AR agonists directed at the human receptor showed promising results in their ability to increase energy expenditure in humans after a single dose.…”
Section: B Progress and Difficulties In Target Explorationmentioning
confidence: 99%
“…However, they do not seem to be able to sustain their effects when administered chronically. Further clinical testing will be necessary, using compounds with improved oral bioavailability and potency, to help assess the physiology of the ␤ 3 -AR in humans and its attractiveness as a potential therapeutic for the treatment of type 2 diabetes and obesity (de Souza and Burkey, 2001).…”
Section: B Progress and Difficulties In Target Explorationmentioning
confidence: 99%
“…Human clinical trials with these agents for use in treating metabolic disorders, however, have been disappointing due to a lack of efficacy or an unfavorable side-effect profile. 8,9) The clinical failure of such compounds has been attributed to a lack of sufficient β3-AR potency and selectivity relative to β1-and β2-ARs resulting from pharmacologic differences between rodent and human receptors, a notion supported by the discovery, cloning, and characterization of the human, rat, and mouse β3-ARs. [10][11][12] Recent studies have indicated that, in addition to adipocytes, the β3-AR is also distributed in human urinary bladder detrusor tissue and its relaxation occurs mainly via β3-AR.…”
mentioning
confidence: 99%